A participatory approach for hydrometeorological monitoring in the Blue Nile River Basin of Ethiopia - Zemadim, Birhanu; McCartney, Matthew P.; Langan, Simon J.; Sharma, Bharat R. (International Water Management Institute, 2013)
Participatory research is increasingly recognized as being useful for conducting multiple activities in research for development projects. The co-learning environment created in participatory research helps to identify existing social and technological gaps, and develop possible solutions to improve the livelihoods of rural communities. This report describes a participatory approach used in the establishment and implementation of hydrometeorological monitoring networks in the Blue Nile River Basin of Ethiopia. The networks were established with the involvement of rural communities and other stakeholders to gain insights into the hydrological processes of the watersheds, in order to improve rainwater management strategies. Local people were involved in the day-to-day management and maintenance of the networks. The participatory approach proved beneficial for several reasons, not least, because it instilled trust and goodwill amongst the communities.